A Review on the Earthquake Resistance Building and the Effect of Earthquake In Sabah - Idris, Nur'ain; Nur Solihin, Ahmad; Edmond, Leonmund; Murugiah, Jaswint; Mohd Noh, Hamidun (Multidisciplinary Applied Research and Innovation, 2020)
This paper presents the compilation of research of earthquake events in Sabah done by past researchers. Earthquake is one of the major natural disasters in Sabah. They affect social and economic life and education negatively. In some countries in this world, multi-storied buildings are usually build due to two factors which is scarcity of land and high cost. Most builders and architects come up with asymmetrical plan configurations to utilize maximum land area. When these plans are constructed in seismic prone areas, they are easily damaged by earthquake. Designation and construction of buildings should be made in a proper and detailed way. Concept of earthquake resistance design explains that buildings should be constructed and designed to resist the forces. Earthquake resistance building was introduced to minimize the damage effect caused by sudden shaking of ground. Seismic waves that reach the Earth’s surface makes the ground to vibrate at certain frequencies. Due to this, the buildings and infrastructures near the vibrating area will start to sway forward and backwards thus creating unimaginable destruction. There are few factors considered for designation and construction of earthquake resistance buildings which are structural configuration, lateral stiffness, lateral strength and ductility. In other factors, aesthetics, functionality and comfort of the buildings should also be considered. Methodology of this study focuses on three main aspects which is the review of earthquake event in Sabah as well as the causes and effects. This study was carried out in order to review the earthquake event. After reviewing it, the collection of data obtained will be analyzed for result and discussion. It consists of 30 research paper and journals that mainly discuss about the methods, the equipment used and observation of earthquake effect towards the community of Sabah.